2016
DOI: 10.1002/ajcp.12030
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness of Military Members to Seek Help: The Role of Social Involvement and Social Responsibility

Abstract: Anchored in the social organization theory of action and change, we use data from a large sample of active-duty Air Force members to examine the direct and indirect influence of social involvement and social responsibility on willingness to seek help in times of need via trust in formal systems and informal supports. Group comparisons are conducted between junior male, junior female, senior male, and senior female service members. The key mediational path in the model for all groups is the connection between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…7. Military members are more likely to seek help when needed if they are socially involved in the community (e.g., participates in unit-, base-or community-sponsored events, which include formal systems and informal networks; Bowen, Jensen, Martin, & Mancini, 2016). 8.…”
Section: Moving Forward: Future Militarymentioning
confidence: 99%
See 1 more Smart Citation
“…7. Military members are more likely to seek help when needed if they are socially involved in the community (e.g., participates in unit-, base-or community-sponsored events, which include formal systems and informal networks; Bowen, Jensen, Martin, & Mancini, 2016). 8.…”
Section: Moving Forward: Future Militarymentioning
confidence: 99%
“…8. Shared responsibility (e.g., concern for others, reaching out to help others get connected to resources) is related to military members' willingness to seek help (Bowen, Jensen, Martin, & Mancini, 2016). 9.…”
Section: Moving Forward: Future Militarymentioning
confidence: 99%
“…Two primary components of community according to the SOAC are informal networks of friends, neighbors, work associates, and extended family members, and formal systems of agencies, organizations, and the professionals that staff them. In particular, earlier research emanating from this framework identified the unique role that military leaders and comrades have on individual and family well‐being, which, in a sense, represents the functioning of informal networks within a formal system called the military unit (Bowen, Jensen, Martin, & Mancini, ; Bowen et al., ). Consequently, we revisit that important element related to leaders and comrades in the current study, considering a range of community connection indicators that may have a bearing on how well families do on a daily basis with everyday life challenges (Mancini & Bowen, ).…”
Section: Theoretical Perspectives On Contexts Processes and Well‐beingmentioning
confidence: 99%
“…Members of the military community can provide a particularly helpful level of support and camaraderie to each other because of the shared experiences of military life (DeGraff, O'Neal, & Mancini, ). Research has found that both broader community networks and networks within the military community play a pivotal role in the well‐being of military members and families (Bowen et al., ; DeGraff et al., ). There is also a geographic, or structural, element of community that has significance, in addition to community as defined by relationships and association.…”
Section: Theoretical Perspectives On Contexts Processes and Well‐beingmentioning
confidence: 99%
“…From this approach, community members’ interactions with each other are thought to build social capital , which is the reciprocal exchange of information and trust that develops from these successful exchanges (Bowen et al., ; Mancini & Bowen, ; Putnam, ). Recently, Bowen, Jensen, Martin and Mancini () employed this social organizational framework to examine the willingness of military members to seek help, and report that trust in formal systems (the military support system particularly) is a major bridge between community involvement and help‐seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%